Review of the Role of Trade in the Work of the Fund. (Policy Papers; Policy Paper ;, 2015)
This review follows the Board-endorsed recommendation by the IEO in 2009 to have an assessment of the Fund's work on trade every five years. In addition to reviewing past work, this paper discusses key issues going forward towards a future trade agenda for the next five years. This reflects the need to operationalize the implications of the changing trade landscape, including the changing drivers of trade-such as global value chains (GVCs)-and the movement of the fulcrum of trade policy from multilateral rounds to regional and plurilateral deals.